IMPLEMENTATION OF POLICIES FOR THE PREVENTION AND HANDLING OF SEXUAL VIOLENCE AT UNIVERSITY XYZ SUKABUMI - Puspita Handayani; Rizki Hegia Sampurna; Dine Meigawati (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Sexual violence in higher education institutions is a serious issue that affects victims’ mental health, well-being, and academic performance. Based on data from 2021 to 2024 from MoECRT, 310 cases of violence were reported, with sexual violence being the most prevalent, accounting for 49.7% of the total reports. In response, the government issued MoECRT Regulation Number 30 of 2021, which mandates the establishment of ToPH of Sexual Violence on every campus. University XYZ Sukabumi formed its ToPH on September 20, 2023. However, the implementation of this policy still faces various challenges. This study aims to analyze the implementation of the policy at University XYZ Sukabumi and identify the obstacles in its execution. The research adopts a descriptive qualitative approach, using data collection methods such as observation, in-depth interviews with key informants Vice Rector I, the head of the ToPH, and students at University XYZ Sukabumi, as well as documentation review. Grindle's (1980) policy implementation theory is used as the analytical framework, focusing on two dimensions: content of policy and context of implementation. The analysis reveals that the content of policy dimension remains suboptimal. Although there have been progressive efforts, such as the establishment of the ToPH and collaboration with professional partners, significant obstacles persist. These include a dependent decision-making structure, lack of specific guidelines, low capacity of program implementers, limited facilities and information, and benefits of the policy that have not been evenly felt by the target groups. Meanwhile, the context of implementation dimension shows that the success of the policy is hindered by weak structural commitment, a organizational culture, and a procedural approach that does not fully side with the victims. It can thus be concluded that the implementation of the policy on the prevention and handling of sexual violence has not yet been successful.